Bispecific Antibody Armed Metabolically Enhanced Headless CAR T Cells - Thakur, Archana; Scholler, John; Kubicka, Ewa; Bliemeister, Edwin T.; Schalk, Dana L.; June, Carl H.; Lum, Lawrence G. (Frontiers in Immunology, 2021)
Adoptive T cell therapies for solid tumors is challenging. We generated metabolically enhanced co-activated-T cells by transducing intracellular co-stimulatory (41BB, ICOS or ICOS-27) and CD3ζ T cell receptor signaling domains followed by arming with bispecific antibodies (BiAbs) to produce armed “Headless CAR T cells” (hCART). Various hCART armed with BiAb directed at CD3ϵ and various tumor associated antigens were tested for: 1) specific cytotoxicity against solid tumors targets; 2) repeated and dual sequential cytotoxicity; 3) survival and cytotoxicity under in vitro hypoxic condition; and 4) cytokine secretion. The 41BBζ transduced hCART (hCART41BBζ) armed with HER2 BiAb (HER2 hCART41BBζ) or armed with EGFR BiAb (EGFR hCART41BBζ) killed multiple tumor lines significantly better than control T cells and secreted Th1 cytokines/chemokines upon tumor engagement at effector to target ratio (E:T) of 2:1 or 1:1. HER2 hCART serially killed tumor targets up to 14 days. Sequential targeting of EGFR or HER2 positive tumors with HER2 hCART41BBζ followed by EGFR hCART41BBζ showed significantly increased cytotoxicity compared single antigen targeting and continue to kill under in vitro hypoxic conditions. In summary, metabolically enhanced headless CAR T cells are effective serial killers of tumor targets, secrete cytokines and chemokines, and continue to kill under in vitro hypoxic condition.